2021
DOI: 10.1136/annrheumdis-2021-220588
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence on ‘Factors associated with COVID-19-related death in people with rheumatic diseases: results from the COVID-19 Global Rheumatology Alliance physician-reported registry’

Abstract: Medications are based on information from the most recent survey or at the time of developing COVID-19. Patients could be taking more than one medication. *P value determined by Wald's test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…methotrexate, azathioprine) as monotherapy or in combination with other drugs and the use of high doses of glucocorticoids in the treatment of inflammatory rheumatic diseases have been detected as factors that result in an adverse outcome of COVID-19, and consequently in an increased mortality rate. (5,6,11,12) The absence of deaths caused by COVID-19 in our cohort can also be explained by the fact that only one severely ill patient was receiving glucocorticoid therapy at the time. Zaključno, rezultati našega retrospektivnog istraživanja sugeriraju da su viša aktivnost upalne reumatske bolesti i popratni komorbiditeti povezani s teškim i kritičnim oblikom infekcije virusom SARS-CoV-2, ali bez smrtnog ishoda.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…methotrexate, azathioprine) as monotherapy or in combination with other drugs and the use of high doses of glucocorticoids in the treatment of inflammatory rheumatic diseases have been detected as factors that result in an adverse outcome of COVID-19, and consequently in an increased mortality rate. (5,6,11,12) The absence of deaths caused by COVID-19 in our cohort can also be explained by the fact that only one severely ill patient was receiving glucocorticoid therapy at the time. Zaključno, rezultati našega retrospektivnog istraživanja sugeriraju da su viša aktivnost upalne reumatske bolesti i popratni komorbiditeti povezani s teškim i kritičnim oblikom infekcije virusom SARS-CoV-2, ali bez smrtnog ishoda.…”
Section: Discussionmentioning
confidence: 84%
“…General risk factors for an adverse course and outcome of COVID-19 in people with inflammatory rheumatic diseases, as well as a higher rate of hospitalization and mortality, are the following: male gender, older age, cardiovascular and pulmonary diseases, chronic kidney disease, moderate to high level of inflammatory rheumatic disease activity and the diagnosis of inflammatory rheumatic disease. (11)(12)(13)(14)) Some studies have found that patients with PsA had a more favourable outcome of COVID-19 compared to patients with RA, but the real reason for this has not yet been determined. (12) It is an interesting fact that none of our subjects diagnosed with PsA had psoriatic manifestations on the skin and/or nails.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 , 33 , 34 , 35 In addition, a survey found that TNF inhibitor treatment did not impact subjective scores ascribed by patients with spondyloarthritis to the severity of their COVID‐19. 36 …”
Section: Discussionmentioning
confidence: 99%